6-MONTH-OLD INFANT WITH LISSENCEPHALY TYPE I ASSOCIATED WITH MILLER DIEKER SYNDROME: A CASE REPORT - Asih, Dewi; Ernes, Audrina (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2024)
Central Nervous System (CNS) malformations occur in 14/10,000 births. Lissencephaly is a rare spectrum of Congenital Brain Malformations (CBM) caused by genetic and non-genetic factors. Lissencephaly consists of type I and type II resulting from disrupted neuronal migration during brain development and is associated with Miller-Dieker syndrome (MDs), Fukuyama Congenital Muscular Dystrophy (FCMD), Muscle-Eye-Brain Disease (MEBD), and Walker-Warburg syndrome (WWs). Type I lissencephaly is associated with MDs, while type II is associated with FCMD, MEBD, and WWs. A 6-month-old infant presented to the emergency department of Royal Prima Medan Hospital with recurrent seizures since 5 days prior to admission, which had been observed since the age of 1.5 months without fever. The patient exhibits facial dysmorphism, growth and developmental delay, with moderate PDA and small ASD (echocardiography), and abnormal EEG and CT findings. Lissencephaly is a rare cortical developmental malformation. MDs is a genetic condition caused by a deletion on chromosome 17p13.3 with characteristics of type I lissencephaly, facial dysmorphism, and severe neurological abnormalities. MDs is a rare chromosomal anomaly and accurately diagnosing based on clinical findings alone can be challenging, thus use of Head CT scan is essential in this case.